The Influence of the Toxin-Producing Dinoflagellate, Alexandrium catenella (1119/27), on the Survival and Reproduction of the Marine Copepod, Acartia tonsa, During Prolonged Exposure - Abdulhussain, Ali H.; Cook, Kathryn B.; Turner, Andrew D.; Lewis, Adam M.; Bibby, Thomas S.; Mayor, Daniel J. (Frontiers in Marine Science, 2021)
Copepods can feed on, and may regulate, the blooms of harmful algae (HA), and may also facilitate dinoflagellate blooms, partly by inducing toxin production and through selective grazing. However, exposure to HA may also cause mortality and reproductive impairment in copepods, with detrimental effects at the population-scale. Here we present the toxin profile of the dinoflagellate, Alexandrium catenella (formerly Alexandrium tamarense), and examine how it affects the survival and reproduction of the cosmopolitan marine copepod, Acartia tonsa. Healthy adult copepods were exposed to mono-specific diets of toxic and non-toxic strains of A. catenella (1119/27 and 1119/19, respectively) and non-toxic Rhodomonas sp. for 10 days alongside unfed controls to examine how their survival was influenced by likely HA bloom conditions. Additional 2-day experiments examined how their egg production rate and hatching success were affected by food deprivation, toxic A. catenella, a non-toxic alternative and a mixture of toxic and non-toxic prey, at high and low concentrations. Survival of A. tonsa declined over the 10-day experiment in all treatments but was not significantly lower in the toxic A. catenella treatment; mortality was only significantly enhanced in the unfed animals, which showed 100 % mortality after 9 days. Egg production rates and hatching success from females in the unfed and toxic A. catenella treatments were all significantly lower than values observed in females fed Rhodomonas sp. or non-toxic A. catenella. Animals offered 1,000 µg C L-1 of Rhodomonas sp. and a 50:50 mixture of toxic A. catenella and Rhodomonas sp. produced significantly more eggs than animals fed toxic A. catenella alone. These results were not apparent at prey concentrations of 100 µg C L-1. The percentages of eggs to successfully hatch from females offered mono-specific diets of toxic A. catenella were always close to zero. Collectively, our results indicate that adult female A. tonsa can acquire sufficient energy from toxic A. catenella to survive, but suffer reproductive impairment when feeding on this prey alone.